Interactive Teaching Material Design Based on Articulate Storyline in Creative Writing Learning Comic Material - Muhammad Rafi; Asnawi (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
The availability of interactive teaching materials specifically designed to support the creative writing learning process is still minimal. This presents an obstacle to creating inclusive learning environments. This study aims to develop interactive teaching materials based on articulate storylines in creative writing learning on comic material. This study uses the ADDIE model. This study employs a Pre-Experimental Design, which involves only one experimental class without a control class, utilizing a One-Group Pretest-Posttest Design model. Data collection techniques include questionnaires, essay pretests, and posttests. The results of the media aspect achieved a percentage of 93% with a very valid/practical category, the language aspect achieved a percentage of 90% with a very valid/practical category, and the material aspect achieved a percentage of 94% with a very valid/practical category. With a very valid category. The average pretest score was 75, and the average posttest score increased to 82. However, since the data were not normally distributed (based on the Shapiro-Wilk test), the Wilcoxon test was employed as a non-parametric alternative. The Wilcoxon test results showed a significant difference between the pretest and posttest. The study's conclusion reveals a substantial difference in student learning outcomes between using interactive learning materials based on articulate storylines in the form of learning applications for comic materials and not using them. The implications of using interactive learning media based on articulate storylines have been proven effective in improving student learning outcomes in creative writing courses, particularly in the context of comic materials.